2013
DOI: 10.1007/s00395-013-0344-2
|View full text |Cite
|
Sign up to set email alerts
|

Targeted ablation of the histidine-rich Ca2+-binding protein (HRC) gene is associated with abnormal SR Ca2+-cycling and severe pathology under pressure-overload stress

Abstract: The histidine-rich Ca2+-binding protein (HRC) is located in the lumen of the sarcoplasmic reticulum (SR) and exhibits high capacity Ca2+ binding properties. Overexpression of HRC in the heart resulted in impaired SR Ca2+ uptake and depressed relaxation through its interaction with SERCA2a. However, the functional significance of HRC in overall regulation of calcium cycling and contractility is not currently well defined. To further elucidate the role of HRC in vivo under physiological and pathophysiological co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 50 publications
4
27
0
Order By: Relevance
“…Recent studies demonstrated that HRC interacted with SERCA and RyR to regulate SR Ca 2+ -uptake and Ca 2+ -release in heart [6, 27], but ParK CS et al showed that poorly regulated SR Ca 2+ -cycling in HRC-KO hearts was not associated with the expressions of SERCA and RyR [17]. Consistent with previous researches [7, 28], our study also confirmed that HRC could influence intracellular calcium.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Recent studies demonstrated that HRC interacted with SERCA and RyR to regulate SR Ca 2+ -uptake and Ca 2+ -release in heart [6, 27], but ParK CS et al showed that poorly regulated SR Ca 2+ -cycling in HRC-KO hearts was not associated with the expressions of SERCA and RyR [17]. Consistent with previous researches [7, 28], our study also confirmed that HRC could influence intracellular calcium.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, a number of known molecular players in cellular Ca 2+ homeostasis, including annexins and S100 proteins, have been implicated in tumor invasion and metastasis [1416]. Substantial evidences suggest that HRC plays a critical role in Ca 2+ -homeostasis [17], but the role of HRC in the occurrence and development of cancer has not been investigated so far.…”
Section: Introductionmentioning
confidence: 99%
“…One of them is the small anti-apoptotic HS-1 associated protein X-1 (HAX1), which interacts with PLN and regulates SR Ca-cycling and contractility [5]. The other one is the histidine-rich calcium binding protein, HRC, which interacts with SERCA2a as well as the ryanodine receptor Ca release complex [6], mediating regulation of both SR Ca-uptake and release [7]. …”
Section: Introductionmentioning
confidence: 99%
“…Conversely, ablation of HRC results in significantly enhanced contractility, Ca transients, and maximal SR Ca uptake rates. However, HRCdeficient cardiomyocytes develop aftercontractions at a significantly higher frequency, compared with wild-type (WT) cells under stress conditions (8). Interestingly, HRC protein levels are reduced both in animal models of heart failure and in failing human hearts (9).…”
mentioning
confidence: 99%
“…We previously demonstrated that S96A-HRC and Hrc null (HRC KO) mouse cardiomyocytes increased arrhythmogenic features under stress in comparison to Ser96-HRC cardiomyocytes (8,11). The S96A-HRC cells also displayed hyperactive RyR2 activity that resulted in aftercontractions (11).…”
mentioning
confidence: 99%